PELAKSANAAN USAHA KESEHATAN SEKOLAH DI SEKOLAH DASAR NEGERI SE KECAMATAN SUMBERLAWANG KABUPATEN SRAGEN TAHUN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
This survey research aimed to det ermine the impl ementat ion of the School Heal th Unit in a Districtelementary school Sumberlawang Sragen Year 2012/2013. This st udy used a questionnaire instrument i sclosed. The populat i on in this st udy were 28 elementary school in the District Sumberl awang Sragen.Sampl ing was done by total sampling, which is 28 El ementary School in District Sumberlawang. Thequest ionnaire has previousl y been t est ed in SD in Batang regency. Af ter val id and reliable then thequest ionnaire used in the st udy. The resul ts of this research is the i mplement ation of t he School Healt h Uni t ina Dist rict element ary school Sumberkawang Sragen wi th an average percentage of 76.25%, shows have beengoing well . Implementation of the School Heal th Unit (UKS) is inf l uenced by a good three indicat ors, namel yhealt h education with t he percentage of 83.10%, good health care with t he percentage of 66.30%, and fosteringa healthy environment 79.30%. Based on the results of this study concl uded that the implementation of theSchool Healt h Unit District Sumberl awang se Sragen year 2012/2013 has been going wel l.